Computational Logic in Multi-Agent Systems 14th International Workshop, CLIMA XIV, Corunna, Spain, September 16-18, 2013, Proceedings - Leite, João; Son, Tran Cao; Torroni, Paolo; van der Torre, Leon; Woltran, Stefan (Lecture Notes in Artificial Intelligence, 2013)
This book constitutes the proceedings of the 14th International Workshop on Computational Logic in Multi-Agent Systems, CLIMA XIV, held in Corunna, Spain, in September 2013. The 23 regular papers were carefully reviewed and selected from 44 submissions and presented with four invited talks. The purpose of the CLIMA workshops is to provide a forum for discussing techniques, based on computational logic, for representing, programming and reasoning about agents and multi-agent systems in a formal way. This edition will feature two special sessions: Argumentation Technologies and Norms and Normative Multi-Agent Systems.